The Tension Between Combating Terrorism and Protecting the Right to a Fair Trial in Indonesia - Istiqomah, Milda; Alimardani, Armin (Lentera Hukum, 2023)
A consistent criticism of the Indonesian criminal justice system indicates its dysfunctional judicial system plagued by systemic corruption and government interference. Given the high profiles of terrorism offences and their strict punishment, it is essential to maintain consistency in sentencing decisions for these crimes. However, there is a significant lack of evidence-based studies of sentencing in Indonesian courts, and none specifically related to terrorism offences. The aim of this study is to analyse the application of the right to a fair trial in sentencing terrorism offences in Indonesia through the interpretive lens of Southern criminology. This study takes a multi-dimensional approach of historical, legal, and empirical analyses to provide an in-depth understanding of factors that affect sentencing decisions in terrorism cases. First, the historical analysis explains that prosecutions for terrorism today include radical Islamists, minority extremists and separatist groups willing to resort to violence against the state and society to achieve their goals. Second, the legal analysis highlights how the existing sentencing regimes provide limited guidance for judges when determining the appropriate punishment for terrorist offenders, frequently leading to prison sentences exceeding 10 years. Third, qualitative analysis further explains that judges use their discretion to avoid the minimum mandatory sentence in specific circumstances, such as in the case of juvenile offenders. A Southern criminology approach helps explain terrorism sentencing in the broader historical, legal, and socio-political contexts. Ultimately, the way laws are written and how judges determine the sentences of terrorism offences result from the persistent impact of colonialism, authoritarianism, and the 'war on terror' discourse. The case study reveals violations of international human rights rules and standards. Terrorism sentencing practices also exemplify a troubling trend where national security trumps the fundamental procedural rights of terrorist offenders.Keywords: Sentencing Decisions, Southern Criminology, Terrorism.